Stage dependency of high-temperature effect on homoeologous chromosome pairing in wheat-rye F1 plants - Kato, T. (Hiroshima Agricultural Coll., Higashihiroshima (Japan)); Yamagata, H (Idengaku zasshi, 1982)
Using two tetraploid wheat-rye F1 lines with and without 5B chromosome, it was examined whether the effect of high temperature (30°C) on homoeologous chromosome pairing varied or not depending upon the developmental stage of the treated PMCs. Experimental results clearly showed that the sensitive stage to high temperature occurred in the middle of premeiosis for a brief period, and that this period corresponded to the period demonstrated for homologous pairing in common wheat fairly well. Thus, it was suggested that three genotypes discussed here, those of the two F1s and common wheat, possess a common step for controlling chromosome pairing, and this step is subject to a disturbance by high temperature at the "high-temperature-sensitive stage". The marked increase of homoeologous pairing by temperature- treatment was briefly discussed on its practical significance in wheat breeding.